SECOND ACCOUNT INSTAGRAM SEBAGAI SARANA EKSPRESI DIRI GENERASI Z - Yusriyyah Zahra Putri Yusup; Shabina Ghalya Sufa; Siti Muawanah; Shofia Salsabilla Azahra; Tan Evan Tandiyono (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Social media has transformed the way individuals express and construct their identities in the digital era. Among Generation Z, the use of secondary Instagram accounts, commonly referred to as “second accounts,” has become increasingly popular as an alternative space for communication and self-expression. This study aimed to examine the role of Instagram second accounts as a medium for self-expression among Generation Z users. Employing a qualitative research approach, data were collected through in-depth interviews with Generation Z participants who actively used second accounts on Instagram. The findings indicate that second accounts provide users with greater freedom to express their thoughts, feelings, opinions, and daily experiences without the pressure of maintaining an idealized online image. Unlike primary accounts, which are often used to present a curated and socially desirable identity, second accounts function as more private and authentic spaces where users can communicate with a limited audience of trusted individuals. Furthermore, the use of second accounts contributes to users’ sense of comfort, confidence, and emotional openness in digital interactions. The study concludes that Instagram second accounts serve as an important medium for authentic self-expression and identity exploration among Generation Z.